Gene conversion is involved in the transfer of genetic information between naturally occurring inversions of Drosophila. - Rozas, J.; Aguade, M. (Proceedings of the National Academy of Sciences of the United States of America, 1994)
The DNA sequences of the ribosomal protein 49 (rp49) region were determined for 34 isochromosomal strains of Drosophila subobscura representing two chromosomal arrangements, the OST and the O3 + 4 gene arrangements, which differ by two overlapping inversions. The data reveal that gene conversion is a mechanism responsible for the transfer of genetic information between naturally occurring inversions of Drosophila. The estimated rate of gene transfer by gene conversion at this region, which is close to an inversion breakpoint, is lower than previous estimates obtained experimentally at the rosy (ry) gene in Drosophila melanogaster. Our data indicate that gene arrangements OST and O3 + 4 are monophyletic and rather old (0.58 and 0.73 million years old, respectively).